How does digital transformation impact bank performance? - Lan Nguyen-Thi-Huong; Hung Nguyen-Viet; Anh Nguyen-Phuong; Nguyen Duy Van (Cogent Economics & Finance, 2023)
Digital transformation is a keyword that has not only been mentioned in recent years but is also strongly applied by companies. However, the benefits of digital transformation for companies are still an issue that needs to be researched. Therefore, this study is conducted to determine the dynamics of digital transformation on banking business results. The research was conducted with joint stock commercial banks in Vietnam listed on the stock exchange. Based on text analysis on annual reports to measure banks' digital transformation level from 2015 to 2021. Research results have shown that digital transformation has a negative impact on bank's performance (through the return on assets and return on equity). Furthermore, the study also found that there was a paradoxical situation where COVID-19 increased the profits of banks. This result provides exciting discussions related to digital transformation and bank performance.
Keywords: 330; bank performance; Digital transformation; performance; text analysis